Dalcídio Jurandir: um cronista de O Estado do Pará e de Diretrizes - BARBOSA, Tayana Andreza de Sousa (Universidade Federal do Pará, 2016)
The writer Dalcídio Jurandir (1909-1979) had a long and useful literary production, which resulted in ten novels with Amazon setting and Linha do Parque of Communist orientation. However, his contact with the universe literate is not restricted to his fictional creation, the writer held intense activity in the press in general and the Communist press in particular. This last, due to his involvement with the Brazilian Communist Party (PCB), which was substantial for the grounds of thought "dalcidiano", both as regards the way to see the reality and its operation, as when targeting their artistic creation. Two important journals for which Dalcídio collaborated in the cities in which he resided were the O Estado do Pará and Diretrizes, both of leftist policy orientations although not organically connected to the PCB. These two journals, it is possible to terms with another face of the novelist, who in addition to writing his novels, he ventured down the path of Chronicles. Thus, aim, with this work, do a study of these chronicles, in two newspapers, spanning the years from 1937 to 1944, in order to publicize these texts from writer marajoara and understand how he behaved in the creation of another literary genre.